Pampanga a new medical tourism destination? - Tharayil, Davis Porinchu (2010)
This study examines the preparedness of Pampanga, especially the Clark Special Economic Zone, for a new mode of tourism that is sweeping Southeast Asia: medical tourism. Visiting foreigners are the driving force behind the surge; they are attracted to the availability of inexpensive medical services, health and wellness treatments, and the possibilities of stretching out their retirement capital to include exotic travel. To differentiate the market, the study divides medical tourism into three clusters, namely: Medical travel, Wellness, and Retirement programs. The participants of the study are 96 primary and secondary stakeholders in the medical tourism business and their partners. Surveys, interviews and focus group discussions were conducted to collect data; the responses were then content-analyzed. Findings show that there is a very conducive environment for the development of medical tourism in the area provided that appropriate measures are taken to enable the industry to meet international standards.
Keywords: Medical tourism